Contemporary Approaches to Enhancing Oral Communication Skills in Medical Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In the current era of medical education, there is a growing acknowledgement of the significant importance of proficient professional communication in ensuring the provision of high-quality healthcare services. This study provides a comprehensive examination of contemporary approaches designed to improve the oral communication skills of medical students, which play a crucial role in their development as proficient healthcare practitioners. The approaches employed in this study are characterized by their complex nature, as they incorporate advancements in language theory, educational technology, and pedagogical practices. This study examines the incorporation of clinical reasoning within advanced pedagogical approaches. The value of techniques such as personal clinical archives, case-based learning, and simulation exercises is emphasized in their ability to provide context for medical terminology and concepts. This, in turn, facilitates a more comprehensive knowledge and proficient utilization of professional medical language. Furthermore, this study investigates the significance of interactive and experience learning. The article examines various methodologies, including role-playing, interactions between patients and actors, and exercises involving peer-to-peer communication, in order to evaluate their efficacy in creating authentic and applicable contexts for students to enhance and polish their communication abilities. These methodologies facilitate the integration of academic knowledge and practical application, a crucial aspect of medical education. This highlights the importance of medical students possessing the skills to navigate multiple linguistic and cultural environments, in order to provide effective and compassionate communication with patients from a range of backgrounds. The significance of this component is particularly underscored within the framework of global health concerns, wherein the utmost importance is placed on effective and culturally appropriate communication.